Spectroscopic studies of tungsten samples exposed to intense deuterium and argon plasma streams - Marchenko, A.; Makhlai, V.; Skladnik-Sadowska, E.; Nowakowska-Langier, K.; Zaloga, D.; Sadowski, M.J. (Вопросы атомной науки и техники, 2019)
The use of tungsten (W) as the main plasma facing component (PFC) was proposed for fusion reactors many years ago. Our recent experiments have been focused on spectroscopic studies of tungsten properties under its irradiation by intense plasma streams. Several samples made of pure W or (90 %W + 10 %Cu) alloy have been exposed to deuterium and argon plasma streams generated by the RPI-IBIS multi-rod plasma injector at different experimental conditions. The optical emission spectroscopy (OES) measurements have been carried out as a function of a plasma-stream energy density. The plasma electron density was estimated on the basis of the Stark broadening of the Dβ and Dα spectral lines in a deuterium-plasma stream propagating freely, i.e. without any target, as well as near the irradiated tungsten surface. In this paper the results of a surface analysis of the tungsten samples after their irradiation by pulsed plasma-ion streams, and the influence of those streams on physical and mechanical properties of the irradiated samples, are discussed. A relationship of the structure and properties of the modified surfaces with parameters of the incident plasma-streams is also analyzed. Експерименти були націлені на спектральні дослідження властивостей вольфраму при його опроміненні інтенсивними плазмовими потоками. Використання вольфраму (W) в якості основного компоненту дивертора для термоядерних реакторів було запропоновано багато років тому [1,2]. Декілька зразків чистого вольфраму та 90%W+10%Cu опромінювались потоками дейтерієвої та аргонової плазм, що генерується стрижневим плазмовим інжектором IBIS, при різних експериментальних умовах. Спектральні вимірювання випромінювання плазми приповерхневого шару проводилися в залежності від густини енергії плазмового потоку. Електронна густина плазми оцінювалась заштарківським розширенням спектральних ліній Dβ та Dα як у вільному потоці, так і поблизу поверхні вольфраму. Представлені також результати поверхневого аналізу опромінених зразків вольфраму та впливу плазмових потоків на фізико-механічні властивості вольфраму. Виявлено взаємозв’язок параметрів налітаючого плазмового потоку та ластивостей модифікованих поверхонь. Проведенные эксперименты были направлены на спектральные исследования свойств вольфрама при его облучении интенсивными плазменными потоками. Использование вольфрама (W) в качестве основного компонента дивертора для термоядерных реакторов было предложено много лет назад [1,2]. Несколько образцов из чистого вольфрама и 90%W+10%Cu облучались потоками дейтериевой и аргоновой плазмы, которая генерируется стержневым плазменным инжектором IBIS, при разных экспериментальных условиях. Спектральные измерения излучения плазмы приповерхностного слоя проводились в зависимости от плотности энергии плазменного потока. Электронная плотность плазмы оценивалась на основе штарковского уширения спектральных линий Dβ и Dα как в свободном потоке, так и вблизи поверхности вольфрама. Обсуждаются также результаты поверхностного анализа облученных образцов вольфрама и влияние плазменных потоков на физико-механические свойства вольфрама. Выявлена взаимосвязь параметров налетающего плазменного потока и свойств модифицированных поверхностей.